Strengthening Institutional Aspects of Farmers, Cipanas, Kabupaten Cianjur - Arjuna Rizaldi (EQUATOR SINAR AKADEMIA, 2021)
Cooperative is an institution formed with the aim of prospering members in particular and society in general. This PKM activity was carried out with the aim of raising awareness of Cipanas village farmers, Cianjur Regency to join themselves in a cooperative in order to increase the competitiveness of Cipanas village farmers in general. This activity is carried out through the formulation of a model for strengthening farmer institutions and counseling to farmers in order to raise awareness of farmers to join in forming cooperatives. The result of this activity is the growing awareness of farmers about the importance of joining a cooperative as the first step in forming a cooperative.